Next-Generation Biodegradable Polymers: From Synthesis to Industrial Applications - Khan, Ismat Ullah (New Environmentally-Friendly Materials, 2022)
Biodegradable polymers of the next generation have become a hopeful move towards reducing the increasing environmental issues regarding the problem of plastic pollution. Being made out of renewable bio-based feedstock, these polymers also possess the option of naturally degrading within the environment, minimizing plastic waste and the impact it has on the environment. This review will be discussing the synthesis process, characteristics as well as commercial uses of biodegradable polymers with a given emphasis on their mechanical, thermal, and biodegradability properties. Two to three major advances in the polymerization technologies, materials design and functionality have been discussed in the article and they play a significant role in improving the performance of biodegradable polymers in numerous applications such as in packaging, agriculture, biomedical, and textile industries. Though it has a bright future, there are challenges associated with it, including cost, scalability, performance ceiling, and waste management that still exist, and it is necessary to tackle these problems to complete the mass adoption of biodegradable polymers. The future trends in development of new materials with high performance, low costs and potential with environmental responsibility are addressed where there is a need of continued innovation in this area so as to facilitate more sustainable and circular economy.